Fe3O4@P(DVB/MAA)/Pd composite microspheres: preparation and catalytic degradation performance. Issue 102 (24th October 2016) - Zhang, Baoliang; Wang, Jiqi; Chen, Junjie; Li, Hengyang; Wang, Hai; Zhang, Hepeng
Abstract : Fe3 O4 @P(DVB/MAA)/Pd composite microspheres were synthesized with a combination of coating and loading processes using Fe3 O4 nanoparticles as a core. Abstract : Fe3 O4 @P(DVB/MAA)/Pd composite microspheres were synthesized with a combination of coating and loading processes using Fe3 O4 nanoparticles as a core. A series of characterizations revealed that a combination of Fe3 O4 coated with a thin polymer shell and deposited Pd nanoparticles was successful. The saturation magnetization of Fe3 O4 @P(DVB/MAA)/Pd was 55.2 emu g −1 and the Pd content was 21.3%. Degradation activity studies confirmed that the as-obtained microspheres showed excellent degradation behavior towards RhB. The degradation efficiency of the Fe3 O4 @P(DVB/MAA)/Pd microspheres for rhodamine B (RhB) can reach 99.6% within 90 s. The regenerated catalyst still showed a catalytic degradation percentage of 98% after being used fifteen times. Meanwhile, the obtained catalyst also displayed degradation ability for other organic dyes. Using Fe3 O4 @P(DVB/MAA)/Pd microspheres is a very promising approach for the remediation of wastewater containing organic dyes due to the fast degradation rate, high degradation efficiency and excellent reusability.